Evaluation of the Reggio Approach to Early Education - Pietro Biroli; Daniela Del Boca; James J. Heckman; Lynne Pettler Heckman; Yu Kyung Koh; Sylvi Kuperman; Sidharth Moktan; Chiara D. Pronzato; Anna Ziff (Institute of Labor Economics (IZA), 2017)
We evaluate the Reggio Approach using non-experimental data on individuals from the cities of Reggio Emilia, Parma and Padova belonging to one of five age cohorts: ages 50, 40, 30, 18, and 6 as of 2012. The treated were exposed to municipally offered infant-toddler (ages 0 3) and preschool (ages 3 6) programs. The control group either didn't receive formal childcare or were exposed to programs offered by the state or religious systems. We exploit the city-cohort structure of the data to estimate treatment effects using three strategies: difference-in-differences, matching, and matched-difference-in-differences. Most positive and significant effects are generated from comparisons of the treated with individuals who did not receive formal childcare. Relative to not receiving formal care, the Reggio Approach significantly boosts outcomes related to employment, socio-emotional skills, high school graduation, election participation, and obesity. Comparisons with individuals exposed to alternative forms of childcare do not yield strong patterns of positive and significant effects. This suggests that differences between the Reggio Approach and other alternatives are not sufficiently large to result in significant differences in outcomes. This interpretation is supported by our survey, which documents increasing similarities in the administrative and pedagogical practices of childcare systems in the three cities over time.
Keywords: I21; I26; I28; J13; 330; childcare; early childhood education; Reggio Approach; evaluation; Italian education